1980
DOI: 10.1002/jso.2930150304
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of chemotherapy on human cancer xenografts in nude mice to clinical response in donor patient

Abstract: Responsiveness of experimental chemotherapy on human cancer xenografts in nude mice was directly compared with clinical response to the same chemotherapy in their donor patients. These xenografts were 1 line of rectal cancer (H-26), two lines of gastric cancer (H-08 and H-22), and 1 line of breast cancer (H-62). Experimental chemotherapies studied were single-drug FT-207 to four lines of xenografts and a combination of mitomycin C, 5-FU, and cytosine arabinoside (MFC) to a line of gastric cancer H-08. Single-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Improved pharmacokinetic properties of MEN4901/T-0128 in terms of plasma half-life, tissue distribution, and tumor T-2513 accumulation may account for the effectiveness. Because the efficacies of some drugs in this human cancernude mouse panel correlated well with their clinical outcomes in patients with the same type of cancers (14,16,23,24), the findings provide direct support that MEN4901/T-0128 is more efficacious than CPT-11 and is an excellent candidate for clinical trials for the treatment of solid tumors. Although MEN4901/T-0128 embodies many of the essential properties indicated for clinical success, it is not peerless as other polymer-and polysaccharide-based CPT conjugates have shown comparable pharmacokinetic properties (3, 4, 6 -8, 10, 11).…”
Section: Discussionmentioning
confidence: 62%
“…Improved pharmacokinetic properties of MEN4901/T-0128 in terms of plasma half-life, tissue distribution, and tumor T-2513 accumulation may account for the effectiveness. Because the efficacies of some drugs in this human cancernude mouse panel correlated well with their clinical outcomes in patients with the same type of cancers (14,16,23,24), the findings provide direct support that MEN4901/T-0128 is more efficacious than CPT-11 and is an excellent candidate for clinical trials for the treatment of solid tumors. Although MEN4901/T-0128 embodies many of the essential properties indicated for clinical success, it is not peerless as other polymer-and polysaccharide-based CPT conjugates have shown comparable pharmacokinetic properties (3, 4, 6 -8, 10, 11).…”
Section: Discussionmentioning
confidence: 62%
“…Since human tumor xenografts are among the best models for predicting drug efficacy in clinical settings, [14][15][16] the activity of FK317 against many human tumors xenografted in athymic mice was examined and compared with those of clinically used antitumor agents, MMC, ADR, CDDP, taxol and CPT-11. FK317 could produce regression and/or ≥80% tumor growth inhibition of almost all tumor xenografts examined, except PC-9 and effects.…”
Section: Discussionmentioning
confidence: 99%
“…1,10) In previous experiments, we compared the results of experimental chemotherapy of 17 tumor lines with those of chemotherapy in the original patients and found a good correlation between the responses to chemotherapeutic agents of the original tumors and the cell lines. 11,12) We also analyzed determinant factors for chemosensitivity in the same panel and found that the combination of tumor volume doubling time (VDT) and the vascularity of the tumor correlates well with chemosensitivity. 1,13) Oncogenes and tumor-suppressor genes are believed to be chemosensitivity determinant factors.…”
mentioning
confidence: 99%